If $f \circ g$ is invertible, is $(f \circ g)^{-1} = g^{-1} \circ f^{-1}$?

If not can someone give me a counterexample?

  • 1
    $\begingroup$ A formula which "works" on the real line is $f=\frac 1 x$, but this is not a function as it is undefined at $x=0$. The question does not specify what kinds of objects $f \text{ and } g $ are supposed to be. Precision of language would be easier to specify if the question were more precisely stated. $\endgroup$ – Mark Bennet Jun 25 '12 at 7:08
  • $\begingroup$ Also see math.stackexchange.com/q/2349/8581 $\endgroup$ – mrs Jun 25 '12 at 7:13

It is true if $f$ and $g$ are invertible. You can check this directly by using the definition of inverse function.

But neither $f$ nor $g$ need to be invertible for $f\circ g$ to be invertible. To find a counterexample, I suggest looking for a noninjective $f$ and a nonsurjective $g$.

  • $\begingroup$ I want to add this point to Jonas answer that we should have: $f:A\longrightarrow B$ and $g:B\longrightarrow C$ wherein $A,B$ and $C$ are sets. :) $\endgroup$ – mrs Jun 25 '12 at 7:06

Let $ f:\{0,1\} \rightarrow \{0\} $ be defined by $ f(0) = 0 = f(1) $

and define $ g:\{0\} \rightarrow \{0\} $ with obvious mapping $g(0) = 0$

then $ f \circ g $ is defined from $ \{0\} $ to $ \{0\} $ with $ (f \circ g) (0) = 0 $ and $ (f \circ g)^{-1} (0) = 0 $

but f is not invertible.


In my view. I think if we take them as binary relations, then we would have

$g^{-1} \circ f^{-1}$

=$\left \{(z,x) \in \operatorname{dom}(f^{-1}) \times \operatorname{ran}(g^{-1})|\exists y \in \operatorname{ran}(f^{-1}) \cap \operatorname{dom}(g^{-1})((z,y) \in f^{-1}\land(y,x) \in g^{-1})\right \}$

=$\left \{(z,x) \in \operatorname{ran}(f) \times \operatorname{dom}(g)|\exists y \in \operatorname{dom}(f) \cap \operatorname{ran}(g)((y,z) \in f\land(x,y) \in g)\right \}$

=$\left (\left \{(x,z) \in \operatorname{dom}(g) \times \operatorname{ran}(f)|\exists y \in \operatorname{dom}(f) \cap \operatorname{ran}(g)((y,z) \in f\land(x,y) \in g)\right \}\right )^{-1}$

=$(f\circ g)^{-1}$

That means $g^{-1} \circ f^{-1}=(f\circ g)^{-1}$ always holds regardless of whether they are invertible functions

For the direct proof of invertible function. We need to prove

  1. $dom((f \circ g)^{-1})=dom(g^{-1} \circ f^{-1})$

  2. for all $z \in dom((f \circ g)^{-1})$, $(f \circ g)^{-1}(z)=g^{-1} \circ f^{-1}(z)$


(1) Suppose that $z \in dom((f \circ g)^{-1})$, let $x=(f \circ g)^{-1}(z)$. Then $f \circ g(x)=z$. Hence $f^{-1}(z)=g(x)$. Consequently $g^{-1} \circ f^{-1}(z)=x$. Therefore $z \in dom(g^{-1} \circ f^{-1})$.

Suppose that $z \in dom(g^{-1} \circ f^{-1})$, let $x=g^{-1} \circ f^{-1}(z)$, analogously $x=(f \circ g)^{-1}(z)$.

Therefore $dom((f \circ g)^{-1})=dom(g^{-1} \circ f^{-1})$.

(2) According to the proof of (1) $g^{-1} \circ f^{-1}(z)=(f \circ g)^{-1}(z)$ for all $z$ in the domain of $(f \circ g)^{-1}$.



Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.